2022
DOI: 10.3390/cells11244026
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Induced Stromal Senescence Promoting Aggressiveness of Prostate and Ovarian Cancer

Abstract: Cancer progression is supported by the cross-talk between tumor cells and the surrounding stroma. In this context, senescent cells in the tumor microenvironment contribute to the development of a pro-inflammatory milieu and the acquisition of aggressive traits by cancer cells. Anticancer treatments induce cellular senescence (therapy-induced senescence, TIS) in both tumor and non-cancerous cells, contributing to many detrimental side effects of therapies. Thus, we focused on the effects of chemotherapy on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Another research confirmed that senescent cancer cells induced by ADT escaped growth inhibition and regained malignant capabilities whereby promote the development of CRPC 40 . Furthermore, a recent study showed that anticancer chemotherapy promoted the senescent phenotype of stromal fibroblasts, leading to metabolic changes and secretion of paracrine factors, thereby facilitated the invasion and proliferation of PCa cells 77 …”
Section: Relationship Between Cellular Senescence and Prostate Cancermentioning
confidence: 87%
“…Another research confirmed that senescent cancer cells induced by ADT escaped growth inhibition and regained malignant capabilities whereby promote the development of CRPC 40 . Furthermore, a recent study showed that anticancer chemotherapy promoted the senescent phenotype of stromal fibroblasts, leading to metabolic changes and secretion of paracrine factors, thereby facilitated the invasion and proliferation of PCa cells 77 …”
Section: Relationship Between Cellular Senescence and Prostate Cancermentioning
confidence: 87%
“…Platinum-based therapies, currently used as the first line of treatment for patients with ovarian cancer, are known to induce senescence in cancer cells 67 . Although therapy-induced senescence (TIS) has been considered a desirable outcome of cancer therapy, the activation of the senescence program has been shown to induce the rewiring of cellular metabolism promoting the pro-tumorigenic and pro-metatastic potential of ovarian cancer cells 68 . Here, we show that sin-lncRNA is specifically induced in ovarian cancer cells that undergo senescence and contributes to sustain the metabolic demands to maintain senescence in cancer cells upon drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Decades ago, Krtolica et al demonstrated the capacity of senescent fibroblasts to promote tumorigenesis, indicating cellular senescence as a case of evolutionary antagonistic pleiotropy that, despite restraining tumor growth in the early stages, may nevertheless exhibit pro-tumorigenic effects when senescence occurs in benign stromal cells [ 26 ]. Emerging evidence supports the role of senescent stromal cells as an accomplice in the growth of a variety of epithelial-derived solid tumors [ 52 , 99 , 100 ]. Similarly, recent studies have shown that senescent mesenchymal stromal cells contribute to the development of myeloid tumors [ 101 , 102 , 103 , 104 ].…”
Section: How Senescent Stroma Promotes Tumor Progressionmentioning
confidence: 98%